Marketing Communication in Attracting Students - Meltareza, Ridma; Tawaqal, Rizki Surya (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
In today's highly competitive higher education landscape, the increasing number of universities offering similar programs has intensified the competition for prospective students. As a result, students have become more selective in choosing their educational institutions. To attract the interest of prospective students, universities need to differentiate themselves through effective marketing messages and strategies. This study focuses on Universitas INABA and its efforts to communicate its unique values and advantages in terms of curriculum, facilities, faculty, and learning environment. The research begins with market analysis and identification of a target group of prospective students with similar needs and characteristics. Following market segmentation, Universitas INABA determines key messages to convey to these prospective students, emphasizing academic excellence, modern campus facilities, industry partnerships, and career development support. The selection of communication channels includes an informative and appealing university website, direct interaction through social media platforms, and participation in educational exhibitions. Effective marketing communication plays a vital role in building a positive brand image, increasing awareness and brand awareness, as well as boosting enrollment numbers. Continuous evaluation and improvement are essential for the university's marketing strategies. Data and feedback from prospective students, current students, and alumni are collected to evaluate the effectiveness of the marketing efforts. This research provides insights into the development and implementation of marketing strategies in higher education institutions, with implications for student recruitment and institutional success.